Study of Mandibular Foramen in Adult Human Mandible Bones: An Osteological Study - Gupta, Anil Kumar; Shah, Gaurav Jung; Prasad, Ram Jiban (Journal of Nepalgunj Medical College, 2022)
Introduction: The mandibular foramen is located on the medial surface of the ramus of mandible through which inferior alveolar nerve and vessels pass and supply the lower jaw. For dentists inferior alveolar nerve block is important to anesthetize the lower jaw for conducting various surgical procedures.Aims: To determine the accurate position of mandibular foramen through which inferior alveolar nerve and vessels were passing and supply the lower jaw and its clinical importance.Methods: This study was conducted on 35 dry mandible bones consisting of 70 mandibular foramens of unknown sex. All the important parameters were studied using vernier caliper.Results: The mean distance of mandibular foramen from mandibular notch was 21.00 mm on right side and 20.29 mm on left side, from posterior border was 12.63 mm on right side and 12.37 mm on left side, from angle of mandible was 20.60 mm on right side and 20.46 mm on left side, from base of the mandible was 23.57 mm on right side and 23.6 mm on left side, from anterior border was 16.74 mm on right side and 16.89 mm on left side.Conclusion: The accurate position of mandibular foramen varies. The knowledge of the average distance of mandibular foramen from various landmarks is useful for dental anesthesia and also helps to avoid complications.